Adenosine-mediated hypotension in in vivo guinea-pig: receptors involved and role of NO - Nieri, P (2001)
1. Adenosine produced a biphasic lowering of the mean BP with a drastic bradycardic effect at the highest doses. The first phase hypotensive response was significantly reduced by the nitric oxide (NO) synthase inhibitor L-NAME. 2. The A(2a)/A(2b) agonist NECA produced hypotensive and bradycardic responses similar to those elicited by adenosine, which were not significantly modified by the A(2b) antagonist enprofylline. 3. The A(2a) agonist CGS 21680 did not significantly influence basal HR while induced a hypotensive response antagonized by the A(2a) selective antagonist ZM 241385, and reduced by both L-NAME and the guanylate cyclase inhibitor methylene blue. 4. The A(1) agonist R-PIA showed a dose-dependent decrease in BP with a drastic decrease in HR at the highest doses. The A(1) selective antagonist DPCPX significantly reduced the bradycardic activity and also the hypotensive responses obtained with the lowest doses while it increased those obtained with the highest ones. 5. The A(1)/A(3) agonist APNEA, in the presence of the xanthinic non-selective antagonist 8-pSPT, maintained a significant hypotensive, but not bradycardic, activity, not abolished by the histamine antagonist diphenhydramine. 6. The selective A(3) agonist IB-MECA revealed a weak hypotensive and bradycardic effect, but only at the highest doses. 7. In conclusion, in the systemic cardiovascular response to adenosine two major components may be relevant: an A(2a)- and NO-mediated hypotension, and a bradycardic effect with a consequent hypotension, via atypical A(1) receptors. Finally, an 8-pSPT-resistant hypotensive response not attributable to A(3) receptor-stimulation or to release of histamine by mastocytes or other immune cells was observed.